Optimisation of encapsulated oil properties to maximise asphalt self-healing - Ruiz-Riancho, N (2022)
The development of self-healing materials could make a relevant impact on our economy and environment, especially when the material is as widely used as asphalt. Asphalt mixture is a self-healing material, which implies that its cracks can close autonomously. The limitation is that self-healing occurs very slowly, and cracks tend to open faster than they close. There is evidence that the addition of encapsulated oil into the asphalt mixtures can improve their natural self-healing properties, which could significantly prolong their lifespan. Besides being a sustainable and resilient alternative, it does not require human action to activate the healing process, which is triggered automatically when the material has deteriorated. The oil released by the capsules reduces the viscosity of the bitumen, promoting the ﬁlling of the cracks by bitumen. Properties such as the internal structure, strength, and size of the capsules inﬂuence the oil release. However, in order to commercialise self-healing capsules as an additive for self-healing roads, they must not worsen properties of the road as specified by the Highways Agencies, such as skidding resistance, fatigue durability or rutting resistance. Additionally, the high expenditure on road networks maintenance (around 10 billion euros in 2019 in Europe) is recently generating particular interest in increasing the durability of asphalt pavements. Encapsulated oil could represent a significant reduction of this expenditure from the governments of European countries. In addition to that, the CO2 emissions related to the bitumen demand and traffic jams caused by the conventional maintenance techniques of roads could be significantly reduced. The capsules containing sunflower oil which were investigated in this thesis were manufactured through the ionic gelation of alginate. The strength and the size of the capsules were varied to produce ten different types of capsules and perform a multivariable experimental study that aims to select the capsule size and strength that optimise the asphalt self-healing properties for mitigating reflective cracking, skid resistance, fatigue durability, deformation under loading (rutting) and the amount of oil released in the bitumen. The inﬂuence of capsules’ strength and size in their compressive strength and the inﬂuence of their thermal expansion, thermal resistance and internal structure in the release of the oil were also analyzed. The capability of the encapsulated bitumen rejuvenators to mitigate the reflective cracking effect was assessed by reproducing the traffic-induced reflective cracks in stone mastic asphalt mixtures. Cyclical loading tests were carried out using a laboratory wheel tracker to analyse the fatigue durability, self-healing properties and rutting effect. Furthermore, computerised tomography scanning technology was used to analyse the changes in the internal structure of the capsules inside the asphalt. Finally, Fourier-transform infrared spectrometry was applied to measure the amount of oil released by the capsules. The results showed that the strength of the capsules was inﬂuenced by the pore size of the calcium-alginate structure, the resistance of the capsules to the temperature reached during asphalt mixing and compaction and the fact that approximately 50% of the oil may not be released during self-healing. It was also concluded that the oil released does not influence the skid resistance, that capsules delay the reflective cracking of asphalt and that rutting increases proportionally to the oil released. Finally, a discrete multi-physics model was implemented to investigate the mechanical response (including breakage and release of the internal liquid) of single core–shell capsules under compression as the first step to develop an automated capsule design system. The model combined Smoothed Particle Hydrodynamics for modelling the ﬂuid and the Lattice Spring Model for the elastic membrane. Owing to the meshless nature of discrete multi-physics, the model can easily account for the fracture of the capsule’s shell and the interactions between the internal liquid and the solid shell. The simulations replicated a parallel plate compression test of a single core–shell capsule. The inputs of the model were the size of the capsule, the thickness of the shell, the geometry of the internal structure, the Young’s modulus of the shell material and the density and viscosity of the fluid. The outputs of the model were the fracture type, the maximum force needed for the fracture and the force–displacement curve. The data were validated by reproducing equivalent experimental tests in the laboratory. The simulations accurately reproduced the breakage of capsules with different mechanical properties. The proposed model can be used as a tool for designing capsules that, under stress, break and release their internal liquid at a speciﬁc time.